THE DIFFERENCE OF STUDENT’ SPEAKING ABILITY USING LEARNING AUDIO AND NONAUDIO MATERIAL THROUGH DRILL METHOD - Agus Riyanto (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2012)
The research objective is to: 1) explore the average ability to speak English students majoring in English Education of UMM uses drill methods with nonaudio teaching materials; 2) explore the average English speaking ability of students majoring in English Education of UMM uses drill methods with audio teaching materials, 3) know the difference average of English speaking ability of students majoring in English education of UMM uses drill methods with nonaudio and audio teaching materials.The study was a quasi-experimental research. Using control and experimental classes. The use of two classes is to promote high internal and external validity of the research design. The study population was all students of third semester of Academic Year 2010/2011. The total enrollment was 209 III semesters, divided into four classes. Number of students consists of 57 classes A, 57 classes B, and 49 classes C, and 46 classes D.Based on the results and discussion, the researchers concluded that the achievements of learning English Speaking ability was improved by using media equipped with audio and proper drill methods. Based on the above conclusion, it can be suggested some of the following: 1) Using the audio features of teaching materials to enhance the ability to speak; 2) The frequency of exercise should be sufficient 30 to 60 minutes a day, divided into several times, 30 minutes 2 times a day. Time can be anytime of the day. 3) At the time of listening, to get the most, while students have to say things that are played.